DEFAULT IN THE SALE AND PURCHASE AGREEMENT OF A SHOPHOUSE IN NON-CASH AND ITS CONSEQUENCES ON HEIRS - Panji Maulana; Muhammad Insa Ansari; Teuku Saiful (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
In binding the sale and purchase agreement between two parties must be carried out and obeyed in accordance with Article 1338 paragraph (1) of the Civil Code states that an agreement made legally will bind the parties as binding as the law and become law for them. The agreed agreement will give birth to obligations that must be carried out by the parties, if not carried out, there will be default due to breach of the agreed agreement. As happened between Baniyamin as the buyer and the late Muhammad Husen as the seller in the binding of the shophouse sale and purchase agreement, there was a default due to the seller not delivering the object of sale and purchase, the buyer had fully paid the price of the shophouse but did not get his rights so that the buyer was disadvantaged in the sale and purchase agreement. The results showed that the buyer made several efforts to obtain his compensation rights for defaults made by the heirs starting from family settlements, giving warning letters twice but there was still no response, and filing a default lawsuit to the Court. The heirs' responsibility for the testator's debt initially planned to pay Rp. 50,000,000. This amount is insufficient from the total loss suffered by the buyer, so that at the time of mediation in the Court the buyer gave the option to the heirs to be able to make payments in stages with a minimum of paying half of the total loss suffered, but the heirs were not able to do so.